Side predilections of offending arteries in hemifacial spasm. (July 2016) - Chung, Moonyoung; Han, Inbo; Chung, Sang-Sup; Huh, Ryoong
Highlights: The anterior inferior cerebellar artery (AICA) is a major offender of right hemifacial spasm. The posterior inferior cerebellar (PICA) is a major offender of left hemifacial spasm. Patients with AICA offender was younger than of patients with other offenders. Hemifacial spasm caused by PICA offender is related to sigmoid sinus size. Abstract: The side predilections of various offending arteries in hemifacial spasm (HFS) have not been well studied. The relationship between clinical and radiological features of HFS and offending arteries were investigated in the present study. A retrospective analysis of 370 patients who underwent microvascular decompression for HFS was performed. The patients were divided into four groups based on the offending arteries, namely anterior inferior cerebellar artery (AICA), posterior inferior cerebellar artery (PICA), vertebral artery, and multiple offending arteries. Affected side, age at onset, presence of hypertension, and sigmoid sinus area and dominance were compared between groups. The mean age of patients with a left HFS was significantly greater than that of patients with a right HFS (P = 0.009). The AICA affected primarily the right side and PICA and multiple offending arteries the left side (P < 0.001). Side of sigmoid sinus dominance was significantly different among groups (P < 0.001). The offending arteries in HFS may be related to these differences. AICA was associated with right-sided symptoms, younger age at onset, and presence of left dominant sigmoid sinus, while PICA was associated with left-sided symptoms, older age at onset, and smaller right sigmoid sinus area.